REGULATORY FRAMEWORK BENCHMARK FOR ENERGY STORAGE: THE CASE OF COMPRESSED AIR ENERGY STORAG - Matos, Catarina (2020)
Energy storage has become both a trend and a central need in recent years, due to the increasing integration of intermittent renewable energy into the electrical grids worldwide. Among the different energy storage technologies available, compressed air energy storage (CAES) is one of the few large-scale energy storage technologies. This paper does a two-step benchmark analysis trying to evaluate whether regulatory policies impact the development of CAES projects worldwide and if it does have any influence on the geographical location of CAES projects? First, the overview of energy storage regulatory framework is done aiming to understand the current energy storage policies, how they are being developed, and the identification of main incentives and barriers. Then, a benchmark analysis of CAES projects worldwide was done with the systematization of the available information into five categories: a) general data; b) technological data; c) reservoirs data; d) economics data and e) project status. CAES projects systematization established a connection with the countries/continents where the regulatory framework for energy storage is further developed, showing a direct association between regulatory framework for energy storage and CAES systems development.